Implementation of dbus-based animal structure and function e-modules using book-creator to improve students' critical thinking skills - Rahayu, Rina; Ismawati, Riva; Winarto, Winarto (IAIN Palangka Raya, 2025)
This study aims to implement a DBUS (Discovery-Based Unity of Science) based animal structure and function e-module using the Book-Creator platform. The research method used is a quantitative method with a one-group pretest-posttest design and sampling determined through a purposive sampling technique. The subjects of this study were 2nd-semester students of the Science Education study program at Tidar University. Data were obtained using critical thinking test instruments, which were then analyzed using the normality test, t-paired test, and N-Gain test. The results showed that the implementation of DBUS-based e-modules was effective in improving students' critical thinking skills, with an average N-Gain score in the experimental class of 0.63 with a medium category and 0.17 for the control class with a low category